4CPS-251 Impact of a multidisciplinary team in reducing polypharmacy and treatment complexity in home care patients. (March 2019) - Pagès-Puigdemont, N; Rovira-Illamola, M; Gené, L; Garrell, I; GUerrero, L; Lascorz, A; Martínez, E; Ortega, M; Silva, A; Sans, M; Soy, D
Abstract : Background: Frail and multimorbid patients are often prescribed multiple medications. 1 Polypharmacy, along with drug-drug interactions and potentially inappropriate medications (PIMs), are known as the iatrogenic triad. Consequently, this population has an increased risk of negative health outcomes. Purpose: To review the medication plan of chronic patients in the home care programme by a multidisciplinary team (integrated by doctors, nurses and clinical pharmacists) to adjust and optimize drug therapy and to reduce treatment complexity and polypharmacy. Material and methods: This was a prospective interventional study in a primary care centre. Domiciliary patients were visited by the multidisciplinary team. The clinical pharmacist interviewed the patient and/or caregiver to obtain a comprehensive medication history (including over-the-counter drugs) and to assess medication adherence. The review process was conducted by the multidisciplinary team and consisted of four steps: deprescribing strategies according to current clinical evidence; simplification of the dosing regimen; identification of drug-related problems; and replacement of PIMs. The final medication plan was agreed with the patient and/or caregiver. The Medication Regimen Complexity Index (MRCI) before and after medication review was recorded. 2 Results: Thirty-three patients were included with a median age of 88.1±6.3 (72.7% female). A total of 4.0±1.9 therapy modifications per patient were performed (ranging from 0 to 10). The main modifications (n=132) were: deprescribing (43.2%, in 25 patients), dose or dosage adjustment (25.0%, in 20 patients) and drug substitution (18.9%, in 21 patients). The number of prescribed treatments before and after the review was 11.0±3.8 vs 9.4±3.9, whereas the MRCI was 27.5±11.2 vs 23.6±10.7, respectively. Conclusion: Medication review by a multidisciplinary team is an effective strategy for tailoring drug therapies, reducing polypharmacy and treatment complexity in home care patients. References and/or acknowledgements: 1. Cullinan S, Raae Hansen C, Byrne S, et al . Challenges of deprescribing in the multimorbid patient. Eur J Hosp Pharm 2017;24:43–6. http://dx.doi.org/10.1136/ejhpharm-2016–000921 2. George J, Phun YT, Bailey MJ, et al. Development and validation of the medication regimen complexity index. Ann Pharmacother 2004;38:1369–76. DOI: 10.1345/aph.1D479 No conflict of interest.